Generation and Evaluation of a New Time-Dependent Dynamic S-Box Algorithm for AES Block Cipher Cryptosystems - Assafli, Hayder T.; Hashim, Ivan A. (IOP conference series. Materials Science and Engineering, 2020)
Cryptographic communication systems depend extensively on the Advanced Encryption Standard (AES) block cipher algorithm. The encryption strength in the AES algorithm is derived from the nonlinearity introduced by the application of s-boxes inside the encryption process. Today, most s-boxes are either static in which the s-box content does not change during the encryption process or dynamic which continuously changes depending on the encryption key. Two major problems exist in such systems that increase the risk of unauthorized decryption. First, the encryption of the same data yields the same cipher key repeatedly. Seconds, the key-dependent s-boxes require sharing the encryption key each time a new s-box is generated. In this paper, a dynamic s-box is introduced that constantly changes independent of the encryption key. The new s-box depends on the epoch timestamp that exists in every digital system as well as transmitted with digital satellite communication systems. The generation of the nonlinear s-box occurs inside the transmitter and receiver identically. The main strength of the proposed approach is that the ciphertext changes while keeping the encryption key constant ensuring different encryption results for the same data. This paper also investigates and analyzes the strength and quality of the new s-box using the avalanche effect method. The results showed that different ciphertext is produced after every encryption process. Moreover, the modified dynamic s-box reached a high avalanche effect exceeding the Strict Avalanche Criterion (SAC).